Mental health literacy and the public perception of persons with depression and schizophrenia in Vietnam - Mobashery, Mahan; Ta, Thi Minh Tam; Cao, Duc Tien; Böge, Kerem; Eilinghoff, Luisa; Nguyen, Van Phi; Mavituna, Selin; Fuchs, Lukas; Weyn-Banningh, Sebastian; Kemna, Solveig; Bajbouj, Malek; Hahn, Eric (Frontiers in Psychiatry, 2024)
BackgroundVietnam’s mental health care system is undergoing significant changes since the government has initiated large-scale programs to reform and develop the mental health care infrastructure. Cultural belief systems on mental illnesses influence help-seeking behavior and compliance. This study investigates the belief systems about people with schizophrenia and depression among people living in the Hanoi area.Method1077 Vietnamese participants answered two open-ended questions after reading an unlabeled vignette describing a character with the symptoms of schizophrenia or depression. The answers were analyzed using thematic analysis.ResultsOf all participants, 88,4% associated the presented cases with a mental illness, with 91,5% in the case of schizophrenia and 85,1% in the case of depression, so both disorders were conceptualized as mental illnesses. 18,6% mentioned depression when presented with the depression vignette, while only 3,6% recognized schizophrenia in the schizophrenia condition.ConclusionsAlmost 9 out of 10 participants considered the presented cases as an example of mental illness, suggesting a high mental health awareness among our participants. The majority did not identify the presented cases as examples of schizophrenia or depression, reflecting little familiarity with Western mental health concepts. It could be interpreted as a sign of relatively low mental health literacy among the study participants.